2023
DOI: 10.3390/atmos14020311
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Bayesian Model Averaging (BMA) for Short-Term Prediction of PM10 Concentration in the Peninsular Malaysia

Abstract: In preparation for the Fourth Industrial Revolution (IR 4.0) in Malaysia, the government envisions a path to environmental sustainability and an improvement in air quality. Air quality measurements were initiated in different backgrounds including urban, suburban, industrial and rural to detect any significant changes in air quality parameters. Due to the dynamic nature of the weather, geographical location and anthropogenic sources, many uncertainties must be considered when dealing with air pollution data. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The bargaining power of suppliers. If suppliers want to affect the profitability of existing enterprises in the industry and the competitiveness of products, they generally achieve this by improving the price of input factors and reducing the quality of unit value (Ramli et al, 2023). However, what input factors it provides to the buyer can mainly determine the strength of the supplier in the competition.…”
Section: Related Materials and Methods Overview Of Marketing Related ...mentioning
confidence: 99%
“…The bargaining power of suppliers. If suppliers want to affect the profitability of existing enterprises in the industry and the competitiveness of products, they generally achieve this by improving the price of input factors and reducing the quality of unit value (Ramli et al, 2023). However, what input factors it provides to the buyer can mainly determine the strength of the supplier in the competition.…”
Section: Related Materials and Methods Overview Of Marketing Related ...mentioning
confidence: 99%
“…In 2016, high levels of SO2 and CO were also detected at the Pasir Gudang monitoring station. In the Bayesian Model Averaging prediction model, Ramli et al [11] discovered that NO2 and PM10 were the most prevalent pollution at Pasir Gudang. Within a radius of two to three kilometres, both residential and business areas can be found in close proximity to the Pasir Gudang monitoring station.…”
Section: Descriptive Of Five Major Air Pollutants (No2 Pm10 O3 So2 An...mentioning
confidence: 99%
“…There have been many studies about the influence of climate variables on air pollutants i.e. particulate matter and sulphur dioxide [38][39][40][41][42][43][44][45][46][47]. In another research, a relationship was found between sulphur dioxide and some climate elements [48].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the researchers, Nejadkoorki and Baroutian [66], and Chaloulakou et al [67] operated an artificial neural network method whereas Chen et al [68] used stepwise regression and wavelet analysis in prediction. Furthermore, Ramli et al used the Bayesian Model Averaging method to estimate the concentration of particulate matter in Malaysia [46]. They used some air pollutants, i.e., NO 2 , SO 2 , CO, O 3 and climate variables i.e., air temperature, wind speed and relative humidity.…”
Section: Introductionmentioning
confidence: 99%